A new species of Sinarella Bryk, 1949 (Lepidoptera, Erebidae, Herminiinae) from Jiangxi, China - Jun Wu; Wen-Yu Liu; Hui-Lin Han (Biodiversity Data Journal)
Sinarella Bryk, 1949 (Erebidae, Herminiinae) is a medium-sized, frail-bodied genus of moths that externally resembles other genera in the Zanclognatha generic complex. All known larvae of this genus feed on fresh leaves of moss. This genus is widely distributed from the Himalayas to Southeast Asia, Japan, Borneo, Sulawesi and New Guinea.A new species of the genus Sinarella Bryk, 1949, S. jinggangshana sp. nov., is described from Jinggangshan National Nature Reserve, Jiangxi Province, China. This species is morphologically similar to S. takasago Wu, Fu & Owada, 2013, S. cristulalis (Staudinger, 1892), S. formosensis Wu, Fu & Owada, 2013 and S. japonica (Butler, 1881), but differs in both external and male genitalia characters. Images of the male adults and their genitalia are provided.